Early changes in ambulatory electrocardiography after transcatheter closure in patients with atrial septal defect and factors affecting heart rate variability - Zhenyang Su; Qing Cao; Hao Zhang; Wei Sun; Haifeng Zhang; Yanhui Sheng; Rong Yang; Xiangqing Kong (BMC Cardiovascular Disorders, 2020)
Abstract Background Factors affecting heart rate variability (HRV) in patients with atrial septal defect (ASD) have not been clarified. This study sought to identify those factors and establish a preliminary risk model. Methods A total of 154 patients with ASD who underwent transcatheter closure and met the study requirements were analyzed in this study. Moreover, 26 patients with patent foramen ovale (PFO) were enrolled in our study as a control group. All patients underwent echocardiography and ambulatory electrocardiography before and one day after the procedure. Results The standard deviation of all normal-to-normal (NN) intervals (SDNN) and the standard deviation of the averages of the NN intervals in all 5 min segments of the entire recording (SDANN) were significantly higher and the heart rate was lower after closure than before closure in patients with ASD (SDNN: 6.08, 95% CI 3.00 to 9.15, p < 0.001; SDANN: 7.57, 95% CI 4.50 to 10.64, p < 0.001; heart rate: -1.17, 95% CI − 2.86 to − 0.48, p = 0.006). Multiple regression analyses indicated that age, sex, defect diameter, heart rate and diabetes were significantly associated with HRV indices (SDNN: R 2  = 0.415; P < 0.001). SDNN and SDANN had obvious correlations with right ventricular systolic pressure (SDNN: R = − 0.370, p < 0.001; SDANN: R = − 0.360, p < 0.001). Conclusions Factors affecting HRV in patients with ASD include age, sex, heart rate, defect size and diabetes. Furthermore, right ventricular systolic pressure plays an important role in the change in HRV.